Concomitant memantine and Lactobacillus plantarum treatment attenuates cognitive impairments in APP/PS1 mice - Wang, Qiu-Jun (Aging (Albany NY), 2020)
Trimethylamine-N-oxide (TMAO) is a gut microbial metabolite that promotes Alzheimer’s disease (AD) progression. Given that probiotics can alleviate AD symptoms by inhibiting the synthesis of TMAO, here we investigated the correlation between TMAO and cognitive deterioration by measuring TMAO levels in the plasma of choline-treated APP/PS1 mice (an AD mouse model) with and without probiotic treatments. We found that declines in L. plantarum in the gut were associated with cognitive impairment. Moreover, 12-weeks of treatment with memantine plus L. plantarum ameliorated cognitive deterioration, decreased Αβ levels in the hippocampus, and protected neuronal integrity and plasticity. These effects were accompanied by reductions in TMAO synthesis and neuroinflammation. These experiments demonstrate that L. plantarum augments the beneficial therapeutic effects of memantine treatment in APP/PS1 mice by remodeling the intestinal microbiota, inhibiting the synthesis of TMAO, and reducing clusterin levels. Our results thus highlight intestinal microbiota as a potential therapeutic target to decrease the risk of AD.